Bink & Gollie, two for one - DiCamillo, Kate (DiCamillo, Kate. Bink & Gollie., 2012)
"The state fair is in town, and now Bink and Gollie-utter opposites and best friends extraordinaire-must use teamwork and their gray matter while navigating its many wonders. Will the energetic Bink win the world's largest donut in the Whack-a-Duck game? Will the artistic Gollie wow the crowd in the talent show? As the undaunted duo steps into the mysterious tent of fortune-teller Madame Prunely, one prediction is crystal clear: this unlikely pair will always be the closest of pals"--